2018
DOI: 10.3390/pharmaceutics10040257
|View full text |Cite
|
Sign up to set email alerts
|

Buccal Bullfrog (Rana catesbeiana Shaw) Oil Emulsion: A Mucoadhesive System Intended for Treatment of Oral Candidiasis

Abstract: Oral candidiasis (OC) is an infectious disease caused by microorganisms of the genus Candida, leading to lesions in the buccal cavity. Its treatment consists of the administration of topical or systemic antifungal agents, which may compromise the patient compliance due to its side effects, highlighting the need for alternative treatments. In this scenario, bullfrog oil, an animal oil composed of a pool of saturated and unsaturated fatty acids, is introduced as a potential antifungal raw material. Thus, the aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…However, despite its broad popular use, especially against inflammatory conditions, there is a lack of scientific evidence supporting such therapeutic property. To date, a limited number of studies have shown scientific evidence of the BFO potential for the development of pharmaceutical products, as showed by previous reports from our research group in which promising antimicrobial and antibiofilm activities were investigated 7,11 . In addition, the cytotoxic activity of BFO not only in natura, but also carried out by nanostructured systems against melanoma cells was also elucidated 6,9 .…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…However, despite its broad popular use, especially against inflammatory conditions, there is a lack of scientific evidence supporting such therapeutic property. To date, a limited number of studies have shown scientific evidence of the BFO potential for the development of pharmaceutical products, as showed by previous reports from our research group in which promising antimicrobial and antibiofilm activities were investigated 7,11 . In addition, the cytotoxic activity of BFO not only in natura, but also carried out by nanostructured systems against melanoma cells was also elucidated 6,9 .…”
mentioning
confidence: 88%
“…Thus, the BFO and BFO-CV at 50, 100 and 200 µg.mL 1 were tested. These concentration were chosen according to previous work of our research group, wherein BFO concentrations up to 0.5 mg.mL 1 were not able to promote cytotoxic effect 11 .…”
Section: In Vitro Cytotoxic Evaluationmentioning
confidence: 99%
“…Natural health products (NHP) have also been studied mainly because of their antioxidant, antiinflammatory and healing effects as well as anticancer activity [64,[75][76][77][78]. In this regard, Buccal Bullfrog (Rana catesbeiana Shaw) oil emulsion was successfully used as a mucoadhesive system to treat oral candidiasis [79]. In addition, curcumin diferuloylmethane, a polyphenolic compound isolated from the rhizomes of the dietary spice turmeric (Curcuma longa), has been studied in experimental models and clinical research particularly for cardiometabolic health and dementia due to its antioxidant and anti-inflammatory properties [80].…”
Section: Medicinal Herb Derivativesmentioning
confidence: 99%
“…It is well known that this oil presents challenging physicochemical and organoleptic characteristics, such as unfavorable smell, flavor, and spreadability, which contribute negatively to therapeutic compliance. 9,11,13 In this context, researchers have developed technological approaches to overcome the undesirable characteristics of BFO. 9,13,14 Davim et al evaluated the anti-inflammatory activity of BFO in natura and a BFO-based microemulsion.…”
Section: Introductionmentioning
confidence: 99%
“…9,11,13 In this context, researchers have developed technological approaches to overcome the undesirable characteristics of BFO. 9,13,14 Davim et al evaluated the anti-inflammatory activity of BFO in natura and a BFO-based microemulsion. This emulsified system theoretically could overcome the disadvantages of BFO in natura.…”
Section: Introductionmentioning
confidence: 99%